Sistem Informasi Rekam Medis Pada Klinik PT. Nippon Paint Jakarta - Siraji, Mohamad; Kuswara, Heri (Journal of Informatic and Information Security, 2020)
Medical record is a file that contains records and documents about patient identity, examination, treatment, actions and other services that have been provided to patients in health care facilities. Problems that occur in the Clinic PT. Nippon Paint Jakarta is an ineffective and efficient management of medical data. This information system aims to manage medical data quickly and accurately. This system development method uses SDLC by making UML diagrams such as use case diagrams, class diagrams, activity diagrams, entity relationship diagrams as stages of system design. This information system is based on WEB using the PHP programming language supported by SQL database. The results of the design of this system are expected to be one of the solutions to the problems that have occurred so far. Keywords: Clinic, Medical Records, Informations Systems Abstrak Rekam medis adalah berkas yang berisi catatan dan dokumen tentang identitas pasien, pemeriksaan, pengobatan, tindakan dan pelayanan lain yang telah diberikan kepada pasien pada sarana pelayanan kesehatan. Permasalahan yang terjadi di Klinik PT. Nippon Paint Jakarta yaitu pengelolaan data medis yang kurang efektif dan efisien. Sistem informasi ini bertujuan supaya pengelolaan data medis dapat berjalan dengan cepat dan tepat. Metode pengembangan sistem ini menggunakan SDLC dengan membuat diagram-diagram UML seperti use case diagram, class diagram, activity diagram, entity relationship diagram sebagai tahapan perancangan sistem. Sistem informasi ini dibuat dengan berbasis WEB menggunakan bahasa pemrograman PHP yang didukung basis data SQL. Hasil rancang bangun sistem ini diharapkan dapat menjadi salah satu solusi dari permasalahan yang terjadi selama ini. Kata kunci: Klinik, Rekam Medis, Sistem Informasi